PENERBITAN SURAT SANGGUP DALAM KASUS BIRO PERJALANAN UMROH FIRST TRAVEL - Mutia Evi Kristy; Elin Sudiarti; Bella Safira Kristianika; Cahya Annisa Utami; Eskaldo Antoni; Faisal Ari Irawan; Hendri Prinata; Hyncha Gabriel Panggabean; Jelita; Okto Rianto Saputra Satya; Sayu Oktalita; Sendy; Yonathan (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
In this paper, we describe the analysis of the issuance of promissory notes by the owner of the umrah travel agency, First Travel, as a commitment to keep their promises or achievements. However, the victims of the failed Umrah departure by First Travel doubted the ability of the First Travel owner. The letter contains four statements regarding his ability to depart for the remaining prospective Umrah pilgrims and the payment of compensation if they cannot be departed. Initially, the pilgrims were directed to collect the payment through the Delay of Debt Payment Obligation (PKPU), but the pilgrims felt that this was not appropriate because they never gave receivables to First Travel. The plaintiffs are victims, not creditors to investors or First Travel partners. This study uses a normative legal approach and the data used are secondary data through literature study.